Rogue waves and Stability Analysis of the new (2+1)-KdV Equation Based on Symbolic Computation Method via Hirota Bilinear Form - Isah, Muhammad Abubakar; Yokus, Asif (Institute of Electrical and Electronics Engineers Inc., 2023)
In this article, we study the novel KdV model which makes a significant contribution to the understanding of a variety of nonlinear occurrences of ion-acoustic waves in plasma and acoustic waves in harmonic crystals. Hirota bilinearization will be used to carry out the task via the proper transformations. For various polynomial functions, several soliton solution types, specifically kink and rogue wave solutions, will be examined. We also present a kink wave and rogue wave interaction solution. The discovered solutions will be illustrated graphically. The existing work is widely used to report a variety of fascinating physical occurrences in the domains of shallow-water waves, ion-acoustic waves in plasma and acoustic waves in harmonic crystals. © 2023 IEEE.
2023 International Conference on Fractional Differentiation and Its Applications, ICFDA 2023 -- 14 March 2023 through 16 March 2023 -- Ajman -- 189775
Keywords: Hirota bilinear method; Kink soliton solution; Rogue waves; Stability analysis; The new KdV equation